The new era of internet governance: technical fragmentation and digital sovereignty entanglements - Radu, R; De Gregorio, G (Rowman & Littlefield, 2023)
The rampant evolution of new technologies, powered by 5G con- nectivity and artificial intelligence (AI) technologies, alters the current status of the internet infrastructure in unprecedented ways. As a result, the internet, as we know it today, will likely change face in the next decade. This chapter argues that this process is driven by an increasing acceleration towards fragmentation on a technical layer and, ultimately, hybridisation in the governance of the internet. Taking the example of the Chinese proposal for an upgrade to the Internet Protocol to support future uses, we reflect on the ways in which a control-prone architecture advances hybridisation along global and local levels, as well as across public and private sectors. A signifi- cant alteration at the level of technical protocols could trigger a much broader paradigm change, affecting global cybersecurity and undermining the protec- tion of fundamental rights via constitutional safeguards.